Effect and mechanism of Yiqing decoction on hyperuricemia rats: Yiqing decoction’s impact on hyperuricemia in rats - Xu, Yajie; Chen, Pan; Sun, Long; Yan Zou; Lixing Zhang; Wanghai Tang; Tingji Zhang; Huo, Jinlin; Zhou, Jin (Cellular and Molecular Biology, 2024)
This study aimed to experimentally compare the uric acid-lowering effect and renal protection of Yiqing Fang in a rat model of hyperuricemia. Additionally, we used network pharmacology to predict the potential active components, targets, and pathways of Yiqing Fang. Male SD rats were randomly divided into control, model, Yiqing Fang, allopurinol, and probenecid groups. Serum creatinine (Scr), blood urea nitrogen (BUN), serum uric acid (UA), alanine transaminase (ALT), complete blood count, and urinary NAG enzyme levels were measured. Standard pathology and electron microscopy samples were prepared from the left kidney to observe renal pathological changes, renal fibrosis, and collagen III expression levels. In addition, we employed network pharmacology to investigate the molecular mechanisms and pathways of Yiqing Fang. The Yiqing Fang group showed significantly lower levels of Scr, BUN, UA, ALT, urinary NAG enzyme, complete blood count, and liver function tests compared to the model group (P < 0.05). Furthermore, both the Yiqing Fang and allopurinol groups exhibited significant reductions in renal pathological changes compared to the model group, along with decreased expression of collagen III. Network pharmacology analysis identified a total of 27 specific sites related to hyperuricemia. The main active components were predicted to include quercetin, berberine, beta-sitosterol, epimedin C, and dioscin. The primary target sites were predicted to include TNF, IL-6, IL-17, IL-1B, and VEGFA. Yiqing Fang may exert its effects through regulation of drug response, urate metabolism, purine compound absorption, inflammation response, lipopolysaccharide response, cytokine activity, and antioxidant activity. These effects may be mediated through signaling pathways such as IL-17, HIF-1, and AGE-RAGE. Yiqing Fang offers potential as a treatment for hyperuricemia due to its multiple active components, targeting of various sites, and engagement of multiple pathways.